Experiências dos discentes do curso de Licenciatura Integrada em Biologia e Química da Universidade Federal do Oeste do Pará no estágio supervisionado remoto - DUARTE NETO, Hozana Firmino (Universidade Federal do Oeste do Pará, 2024)
The health crisis caused by the SARS-CoV-2 virus (Covid-19) caused changes in face-to-face teaching carried out until then in schools, such as the adoption of remote teaching in an emergency. This change had serious consequences in the pedagogical reality of educational institutions and modified the actions of teachers and trainees in several ways. This work is a qualitative approach research that aims to report the experiences lived by undergraduates of the Integrated Degree in Biology and Chemistry of the Federal University of West of Pará in the Supervised Internship in High School carried out exceptionally remotely during the pandemic. Twelve undergraduates who joined in 2016 participated in this research. Data were collected through a questionnaire prepared on the virtual platform Google Forms. The results show that the undergraduates did not find difficulties in accessing the internet and the WhatsApp messaging application was the most used virtual platform/environment by the interns. In addition, despite the evident difficulties of interactions between undergraduates and students of the school units, great learning was reported by the interns with regard to technologies aimed at teaching.